NbJAZ3 is required for jasmonate‐meditated glandular trichome development in Nicotiana benthamiana. Issue 2 (5th April 2022) - Yan, Xiaoxiao; Cui, Lipeng; Liu, Xiangyang; Cui, Yuchao; Wang, Zhaojun; Zhang, Hongying; Chen, Liang; Cui, Hong
Abstract: Exogenous methyl jasmonate (MeJA) treatment induces glandular trichome development in Nicotiana benthamiana, but the function of JAZ proteins, acting as core repressors, and their downstream genes have not been clearly shown in plants. Here, a bioinformatics analysis of 71 JAZ genes from tobacco, Arabidopsis thaliana, and tomato was carried out and shown to share highly conserved domains. Then, the expression profile of 17 NbJAZs in different tissues was analyzed, and NbJAZ3 was highly expressed in trichome. Through transgenic technology, we demonstrated that the glandular trichome density of NbJAZ3 ‐overexpression lines significantly decreased with lower expression levels of NbWo, NbCycB2, and NbMIXTA . In contrast, the trichome density of NbJAZ3 RNAi lines slightly increased with higher expression level of NbWo . Given the negative protein feedback regulation relationship between NbCycB2 and NbWo, we verified that MeJA induced NbWo expression. NbWo was a direct target gene of NbJAZ3 and further demonstrated that NbJAZ3 inhibited the transcriptional activation of NbCycB2 by NbWo . Together, our findings outline a novel JA‐meditated glandular trichome development model consisting of the NbJAZ3‐NbWo‐NbCycB2 axis.